Climatic projections of lightning in southeastern Brazil using CMIP5 models in RCP’s scenarios 4.5 and 8.5 - Santos, Ana Paula Paes dos; Pinto Júnior, Osmar; Santos, Sérgio Rodrigo Quadros dos; Lima, Francisco José Lopes de; Souza, Everaldo Barreiros de; Morais, André Arruda Rodrigues de; Avila, Eldo Edgardo; Pedernera, Débora Analía (2024)
Fil: Santos, Ana Paula Paes dos. National Institute for Space Research; Brazil.